ASSESSING THE DEVELOPMENT AND FUTURE OF MORAL-BASED ACTIONS AND LEADERSHIP IN SCIENCE AND TECHNOLOGY SECTORS IN INDONESIA - Christian Gerald Daniel (OISAA, 2019)
A solid understanding of ethics is one of the most crucial aspect in any technological or scientific progress. Any development proceeded without proper knowledge of ethical value will drive the process to fall under the risk of failure that often damages the surroundings. In this paper, numerous essential ethical theories from various philosophers are elucidated herein to yield a general code of conduct as the basis to analyse several cases in several sectors, such as academic, engineering and medical, in attempt to locate any potential violation of values in accordance to the aforementioned study. Furthermore, several key points regarding the suggested moral virtues are summarised from the ethical code in the respective sectors to gain an understanding of the application of the theorems to the conducts. Lastly, numerous attempts of improvement in each sector; one example is the broader opportunity of conducting research supported by the government, are discussed in the last segment of this paper. The ultimate goal is then to illustrate the development of effort made in each sector in Indonesia learn from the mistakes to improve the condition with respect to the moral virtues and sustainability.